Innovation frequency of durable complementary goods - Chen, Yijuan; ANU College of Business and Economics ([Canberra] : Australian National University, [College of Business & Economics], 2010)
Focused on innovation frequency of durable complementary goods, this paper shows that interdependency of innovation decisions generically gives rise to coordination failure between the producers. More importantly, the coordination failure may arise in opposite directions: Not only may the producers delay introducing new products, they may also introduce new products faster than the social optimum. The possibility of hastened innovations is in contrast to the conclusion from the literature focused on the monopolistic setting. The results provide a caution for policy-makers, and on the other hand serve as benchmarks for future studies incorporating competition.
"JEL codes: O31".
"March 2010".
Title from title screen (viewed on September 16, 2010).
Includes bibliographical references (p. 33-34).
Text.
Mode of access: Internet via the World Wide Web. Available at: http://www.cbe.anu.edu.au/research/papers/pdf/wp515.pdf.
Keywords: Diffusion of innovations -- Econometric models; Durable goods, Consumer -- Econometric models; Equilibrium (Economics) -- Econometric models; New products -- Econometric models